Efek Penambahan Taping pada Intervensi Micro Wave Diathermy dan Stretching Terhadap Pengurangan Nyeri pada Kondisi Plantar Fascitis (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2009)
This Researh aims to detect increasing effect difference existence taping in intervention micro wave mengathermy (mwd) and stretching towards pain reduction in condition plantar fasciitis. method: This research kind quation eksperimental to detect effect a intervention that done towards watchfulness object. Sample is grouped to be two treatment groups, my treatment group consists of 7 person with interventions that given micro wave mengathermy (mwd) and stretching and treatment group ii that consist of 7 person with interventions that given increasing taping in intervention micro wave mengathermy (mwd) and stretching. This watchfulness statistics analysis uses test wilcoxon and man-whitney. Result: with test wilcoxon match pairs in my treatment group demoes value p = 0,018 (p<? =0,05) and in treatment group ii value p = 0,018 (p<? =0,05) mean intervention that done in each group berefek in pain reduction in condition plantar fasciitis. and result mann-whitney demo value p = 0,003 p<? =0,05 that mean there effect significant between my treatment group and treatment group ii. Conclusion: there increasing effect difference taping in intervention micro wave mengathermy and stretching towards pain reduction in condition plantar fasciitis.Keywords: Tapping, Plantar Fascitis, Stretching